Variation of CO Column over North Kerala by Exploring MOPITT Data - Sheela M Joseph; M. K. Satheesh Kumar, Nishanth. T, K. M. Praseed (Recent Research in Science and Technology, 2010)
Carbon Monoxide (CO) is one of the prominent pollutant species mainly produced from of fossil fuel burning and motor vehicles. Being a toxic trace gas, it can considerably affect human health. The rapid increase in CO enhances the production of surface ozone which contributes to global warming. This is the first attempt to retrieve the increase in CO over a column of atmosphere up to 100 mb pressure from the surface using MOPITT version 3 of level 2 data. The increase in column abundance of CO observed is correlated with the increase in vehicles in this region and it gives a positive correlation for the four years of observation from 2004. The prominence of this location of north Kerala is that no major industries are sited within this region and the increase in pollution is solely due to anthropogenic activities. Ã‚Â